Fighting France : from Dunkerque to Belfort - Wharton, Edith, 1862-1937 (Edinburgh University Press, 2015)
A new edition of Edith Wharton's war reportage from the First World War. Edith Wharton was one of the first woman writers to be allowed to visit the war zones in France. This resulting collection of 6 essays presents a fascinating and unique perspective on wartime France by one of America's great novelists. Written with Wharton's distinctive literary skills to advocate American intervention in the war, this little-known war text demonstrates that she was a complex and accomplished propagandist. However, these eyewitness accounts also demonstrate a troubling awareness of the human cost of war. This new critical edition aims to bring this neglected text into the field of Wharton studies, allowing critics and enthusiasts to re-evaluate her contribution as a war writer and to assess the significance of this period for her literary development. Key Features The first scholarly edition of a highly important work in Wharton's oeuvre Restores the original photographs which accompanied the text Provides extensive critical apparatus for understanding the text including a scholarly introduction and authoritative annotation in each chapter Includes archival research in the Edith Wharton Collection at the Beinecke Rare Book and Manuscript Library, Yale University, and the Edith Wharton Manuscripts, Firestone Library, Princeton University
Keywords: Wharton, Edith, -- 1862-1937.; Wharton, Edith, -- 1862-1937; Wharton, Edith -- 1862-1937; World War, 1914-1918 -- France.; World War, 1914-1918 -- Personal narratives, American.; Guerre mondiale, 1914-1918 -- France.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; France; Weltkrieg -- 1914-1918; 1914-1918; Electronic books.; Quelle.; Personal narratives -- American; Personal narratives.; Récits personnels.